Destination Image and Travel Motivation: Impact on Visit Intention, Decision to Visit - Andjarwati, Anik Lestari; Tiarawati, Monika; Indarwati , Tias Andarini (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
The decision to visit is a series of processes in which tourists become aware of the need, acquire information, evaluate information about tourist attractions, determine alternative options, and make the most suitable decision to visit a tourist destination. The destination image plays a crucial role for tourists in the decision-making process of visiting, and motivation is highly significant as a driving factor for the occurrence of the decision to visit. The research objective is to determine the influence of destination image, travel motivation, and visit intention on the decision to visit. This study employs a quantitative method. Data collection is conducted using a survey method with questionnaires distributed to visitors. One hundred and eleven respondents have completed the questionnaire, and data analysis is performed using Path Analysis. The research findings indicate that the destination image directly influences the visit intention and the decision to visit. Travel motivation does not directly influence the visit intention and the decision to visit. The visit intention can act as a partially mediated mediating variable. This research is based solely on one tourist destination in the Trenggalek Regency, East Java Province, Indonesia, so the results cannot be generalized. The theoretical implications are that the decision-making model for visiting is an interconnected sequence that originates from the destination image in the minds of tourists, travel motivation impacts the visit intention, and the visit intention will impact the decision to visit. While several studies on the influence of destination image on the decision to visit have been conducted, research specifically addressing the influence of destination image and travel motivation on the visit intention and the decision to visit has not been extensively explored